2020
DOI: 10.1177/0363546520937302
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Imaging of Ulnar Collateral Ligament Injury: A Systematic Review

Abstract: Background: Ulnar collateral ligament (UCL) injuries can be debilitating in overhead athletes. Accurate diagnosis is important; however, several imaging modalities are available for the assessment of UCL injuries. Purpose: To provide a comprehensive review of published literature regarding the diagnostic capabilities of different imaging modalities for UCL tears. Methods: PubMed, Medline, and Embase were queried for peer-reviewed literature published between January 1947 and June 4, 2019, pertaining to diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Physical education majors participate in more sports than other majors. ey not only attend the elective and compulsory basketball courses offered by the school but also have to participate in basketball training, competition, extracurricular activities, and practices [20]. erefore, in the research, sports injuries of students majoring in physical education are investigated on four occasions, namely, basketball special and compulsory courses, extracurricular activities, training, and competition.…”
Section: Experiments and Analysismentioning
confidence: 99%
“…Physical education majors participate in more sports than other majors. ey not only attend the elective and compulsory basketball courses offered by the school but also have to participate in basketball training, competition, extracurricular activities, and practices [20]. erefore, in the research, sports injuries of students majoring in physical education are investigated on four occasions, namely, basketball special and compulsory courses, extracurricular activities, training, and competition.…”
Section: Experiments and Analysismentioning
confidence: 99%
“…The amount of joint widening is related to the ligament integrity as demonstrated in cadaveric studies with sequential ligament sectioning [ 28 , 31 ] and clinical studies of athletes with confirmed mUCL tears [ 22 ••, 32 34 ]. Multiple SUS techniques have been used in previous studies and have included a variety of force loads and flexion angles while applying stress.…”
Section: Evaluation Of Mucl Function With Stress Ultrasoundmentioning
confidence: 99%
“…On physical exam, patients often have tenderness along the medial elbow at or near the mUCL origin with positive provocative testing, including the moving valgus stress test and milking maneuver. The diagnosis is aided by various imaging modalities, including static radiographs [ 10 13 ], stress radiographs [ 13 16 ], computed tomography (CT) [ 17 ], magnetic resonance imaging (MRI) [ 4 , 17 , 18 , 19 , 20 , 21 , 22 ••, 23 , 24 , 25 , 26 , 27 ], and ultrasound (US) [ 28 – 30 ]. US has been shown to be a low cost, efficient, and non-invasive method to evaluate the mUCL in throwing athletes.…”
Section: Introductionmentioning
confidence: 99%
“…6,8 Imaging modalities that have the greatest accuracy for diagnosis include magnetic resonance imaging (MRI), MRI-arthrogram, and stress ultrasonography. 2,3,11,12 Treatment of UCL injury depends on multiple factors. These include if the injury is a partial tear or complete tear and the location (distal versus proximal) of the partial tear.…”
mentioning
confidence: 99%